Al-khasyah in the Qur’an: An Integrative Framework of Knowledge, Faith, and Ethical Action for Contemporary Society - Muh.Ilham Majid Dohe; Arif Rahman (Pappaseng: International Journal of Islamic Literacy and Society, 2025)
Contemporary societies face a deep moral and spiritual crisis marked by technological acceleration, ethical fragmentation, and declining public trust, which has stimulated renewed scholarly interest in Qur’anic resources for reconstructing moral life. This article examines the concept of al-khasyah as a foundational yet under-theorized principle of Islamic ethics, aiming to clarify its meaning, epistemic roots, and practical relevance for the modern world. The study adopts a qualitative, interpretive, and text-centered methodology grounded in thematic Qur’anic exegesis, integrating close reading of selected verses with comparative analysis of classical and modern tafsir traditions. Primary sources include key passages that link knowledge, fear of God, and righteous action, while secondary sources draw on authorities such as Ibn Kathir, Al-Tabari, Al-Qurthubi, Al-Ghazali, Al-Alusi, and Hamka. Findings show that al-khasyah is a knowledge-based reverence rather than instinctive fear, emerging from contemplative engagement with divine signs in creation and revelation. The Qur’an consistently connects true knowledge with humility before God, positioning al-khasyah as an epistemic, spiritual, and ethical virtue that motivates obedience, accountability, and justice. Fear of the Most Merciful in the unseen cultivates sincerity, self-regulation, and moral resilience, particularly in digital and surveillance-driven contexts. Synthesizing these insights, the study proposes an integrative model of Knowledge, Reverence, Ethical Action, and Spiritual Integrity as the core architecture of Qur’anic moral formation. The article concludes that al-khasyah offers a constructive framework for addressing modern moral deficits by embedding knowledge within transcendental accountability and character-based ethics, with significant implications for education, governance, and social trust and communal ethical renewal.